(untitled) (Philological Studies, 2021)
The paper presents the processes of creating the portal Franček, the first interactive educational language portal with dictionary and grammatical content for Slovenian, and the preparation of language data for the portal. The portal, whose design is original and not based on any other language portal, provides information on the words’ meanings, synonyms, morphological paradigms, pronunciation, phraseology, dialect usage, history, and etymology. This data is linked to two educational grammars and accompanied by teaching materials, a game for smart devices, a language counselling service for teachers, and a description of modern teaching methods. The main purpose of the portal is to introduce students of elementary and secondary schools to the use of various dictionaries, to improve their linguistic and metalinguistic competence, and introduce them to other language resources. The portal fills the gap in existing Slovenian language resources, namely the lack of specialized or appropriately suited comprehensive dictionary manuals, primarily intended for the schooling population and use in education. The paper also presents the creation of new dictionary, grammatical, and teaching content, and the process of its adaptation and consolidation into a new, coherent whole. Due to the age span of target user groups the content and its visualization are adapted to three age groups (elementary-school grades 1 to 5, grades 6 to 9, and secondary school) based on their (meta)linguistic knowledge, while also taking into account the curricula for teaching Slovenian in elementary and secondary school.